Kajian Pengaruh Jenis Pelarut Dan Lama Maserasi Terhadap Karakteristik Dan Stabilitas Ekstrak Jeruk Limau (Citrus Amblycarpa) Sebagai Antioksidan Alami Pada Makanan - Putu Julyantika Nica Dewi; G. P. Ganda Putra; Lutfi Suhendra (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2022)
Lime is a natural ingredient that contains bioactive compounds such as antioxidants (vitamin C, palmitate, polyphenols), essential oils, and high antibacterial properties. The bioactive compounds are obtained by extraction using the maceration method. This study aims to determine the effect of the type of solvent and the time of maceration on the characteristics and stability of the extract of lime (Citrus amblycarpa) as a natural antioxidant in food, and to determine the type of solvent and the most effective maceration time. Extraction of lime using 3 types of solvents (ethanol, methanol, and acetone) and 3 periods of maceration, namely (2 hours, 4 hours, and 6 hours). The variables observed in the first stage were: yield, vitamin C, total phenol, antioxidant capacity), effectiveness index test. The second stage of research was carried out by storing lime extract in a temperature variation treatment consisting of 6 levels (S1 = 0oC, S2 = 20oC S3 = 40oC, S4 = 60oC, S5 = 80oC and S6 = 100oC) then observed the trend rate of vitamin C content. The effectiveness index test showed that the methanol solvent treatment and 6 hours maceration time were able to produce the best lime extract characteristics with yields of 35.08%, vitamin C of 7,580.90 mg AAE / 100g, total phenol of 6,484.54 mg GAE / 100g , and the antioxidant capacity of 4,928.79 mg GAEAC / 100g. The higher the storage temperature, the lower the vitamin C content of the lime extract. Changes in vitamin C content to the effect of temperature are shown by regression y = -11.433x + 7518.6, with a correlation coefficient (r) -0.9251. The highest vitamin C content at 0oC was 7338.47 mg AAE / 100g and the lowest at 100oC was 6163.59 mg AAE / 100g. The results of the study concluded that the type of solvent treatment and maceration time affected the characteristics of the lime extract.